ENHANCING STUDENTS’ PERFORMANCE IN GRAPHING FUNCTIONS THROUGH FLIPPED TEACHING METHOD - De la Cruz, Juvis Gem (International Journal of Arts, Sciences and Education, 2024)
Graphing Functions is one of the essential competencies in General Mathematics that should be mastered by the students. However, based on the latest item analysis, it was found out that this competency has low learning outcome. This study aimed to look into the effectiveness of Flipped Teaching Method in enhancing the performance of Grade 11 students in graphing functions. Using quasi-experimental research design, there were two groups, of 39 students each, were given pre-test about graphing functions. The experimental was exposed to the flipped teaching method while the control was exposed to the traditional way of teaching. The administration of the post- test was done after four (4) class sessions. Using independent samples t-test, the computed p-value is less than 0.001. This implies that there is a significant difference on the post-test scores between the experimental and the control group. Also, the mean post- test score of the students in the experimental group is 17.2821 which is significantly higher than the mean post- test score of the students in the control group that is 13.3077. This is an indication that the performance of the students being exposed to Flipped Teaching Method is better than the students being exposed to the traditional way. Moreover, using the Cohen’s d, with an effect size of 2.413682, Flipped Teaching Method has a great effect in the performance of the students on graphing functions.